Islamic Business Ethics on The Using Bots in The Completion of Daily Quests in The Game Growtopia - Syifa, Muhammad Khoirus; Huda, Nurul; Mukarromah, Lisa Aminatul (Et-Tijarie, 2024)
The mechanism of using bots in the game Growtopia is indicated to violate the principles of Islamic business ethics according to Naqvi's theory. This is because the use of bots can create an imbalance within the game's ecosystem and cause losses to other players. The imbalance refers to the lack of sportsmanship among players. The losses suffered by other players include falling behind in virtual item productivity, and developers also experience losses as this can reduce the integrity of the game developers, who are perceived as unable to provide a healthy ecosystem for players. This research uses a descriptive-qualitative method with data collected through observation, interviews, and documentation. After conducting the research, it was found that the use of bots in Growtopia violates Islamic business ethics principles of balance, free will, and responsibility. While bots can provide efficiency in completing daily tasks, this ultimately undermines the integrity of the game and creates unfairness among players. The use of bots makes the game unfair because players using bots gain unreasonable advantages compared to those who play honestly. Growtopia imposes penalties in the form of bans on accounts detected using bots in the game.